Plastidial Expression of 3β-Hydroxysteroid Dehydrogenase and Progesterone 5β-Reductase Genes Confer Enhanced Salt Tolerance in Tobacco - Sameeullah, Muhammad; Yildirim, Muhammet; Aslam, Noreen; Baloğlu, Mehmet Cengiz; Yucesan, Buhara; Lössl, Andreas G.; Saba, Kiran; Waheed, Mohammad Tahir; Gurel, Ekrem (MDPI AG, 2021)
The short-chain dehydrogenase/reductase (SDR) gene family is widely distributed in all kingdoms of life. The SDR genes, 3β-hydroxysteroid dehydrogenase (3β-HSD) and progesterone 5-β-reductases (P5βR1, P5βR2) play a crucial role in cardenolide biosynthesis pathway in the Digitalis species. However, their role in plant stress, especially in salinity stress management, remains unexplored. In the present study, transplastomic tobacco plants were developed by inserting the 3β-HSD, P5βR1 and P5βR2 genes. The integration of transgenes in plastomes, copy number and transgene expression at transcript and protein level in transplastomic plants were confirmed by PCR, end-to-end PCR, qRT-PCR and Western blot analysis, respectively. Subcellular localization analysis showed that 3β-HSD and P5βR1 are cytoplasmic, and P5βR2 is tonoplast-localized. Transplastomic lines showed enhanced growth in terms of biomass and chlorophyll content compared to wild type (WT) under 300 mM salt stress. Under salt stress, transplastomic lines remained greener without negative impact on shoot or root growth compared to the WT. The salt-tolerant transplastomic lines exhibited enhanced levels of a series of metabolites (sucrose, glutamate, glutamine and proline) under control and NaCl stress. Furthermore, a lower Na+/K+ ratio in transplastomic lines was also observed. The salt tolerance, mediated by plastidial expression of the 3β-HSD, P5βR1 and P5βR2 genes, could be due to the involvement in the upregulation of nitrogen assimilation, osmolytes as well as lower Na+/K+ ratio. Taken together, the plastid-based expression of the SDR genes leading to enhanced salt tolerance, which opens a window for developing saline-tolerant plants via plastid genetic engineering.
Keywords: Nicotiana; Sucrose; Hydroxysteroid Dehydrogenases; glutamate; short chain dehydrogenase/reductase (SDR) genes; Article; β -HSD; Gene Expression Regulation, Plant; Reductase (SDR) Genes; Plastids; Transgenes; proline; Plant Proteins; salt tolerance; Digitalis; sucrose; Salt-Tolerant Plants; Salt Tolerance; Plants, Genetically Modified; NMR; β-HSD; Transplastomic Plants; Short Chain Dehydrogenase; glutamine; Oxidoreductases; transplastomic plants; 2. Zero hunger